Etiquette and behavior during D. Carlos Luiz D'Amour's pastoral travel to south of the diocese of Cuiaba - Marin, Jerri Roberto [UNESP] (Editora Puc Minas, 2015)
This article studies the etiquette diffusion and the reform of behavior during the pastoral visit of D. Carlos Luiz D'Amour, south of the Diocese of Cuiaba, in 1886. The source is the diary written by the private secretary Canon Bento Severiano da Luz. In such diary, the paths of the party were narrated as well as its major events and achievements, having the bishop as the central character. One of the objectives of the trip was to spread new patterns of behavior, feelings and etiquette, civilize Mato Grosso and establish a good Catholic society. The public appearances of the bishop assumed symbolic functions, i.e., the political and religious affirmation of the episcopal power in society, creating a sacred image embodied in his person. D. Carlos, in the game of power relations, sees himself compelled to submit to the etiquette, whose standards were Europeans and the imperial court, as well as to pressure the diocesans to do the same. Every detail of the etiquette and the canonical ceremonial has fulfilled the function of ostentatious self-representation. His suppression has abolished distances, the social distinctions and obliterated his authority and power.
Keywords: etiquette; behavior; pastoral visit; D. Carlos Luiz D'Amour